Banki spółdzielcze na rynku kredytu na nieruchomości w Polsce - Papież, Renata (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The main aim of the article is defining the role of co-operative banks – bothin quantitative and qualitative aspects – on the mortgage market in Poland.Residential and commercial mortgage financing in the Polish banking sector isdominated by a big commercial banks. Both the co-operative banks and specializedmortgage banks have a marginal importance in this market. However, cooperativebanks using their attributes, i.e. better knowledge of the local marketand gradually accumulated know how and experience, increase very slowly theirmarket share.